2020
DOI: 10.1002/jgm.3300
|View full text |Cite
|
Sign up to set email alerts
|

Circ‐PRMT5 promotes breast cancer by the miR‐509‐3p/TCF7L2 axis activating the PI3K/AKT pathway

Abstract: BackgroundBreast cancer is the most prevalent malignancy occurring in females. In recent years, emerging evidence has suggested that circular RNAs are involved in the development of multiple cancers. Circ‐PRMT5 has recently attracted attention as a tumor‐promoting circular RNA. In the present study, we focused on exploring the biological effects of circ‐PRMT5 in breast cancer.MethodsA quantitative real‐time polymerase chain reaction was used to determine the expression of circ‐PRMT5 in breast cancer. In vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…High expression of circPRMT5 is associated with a poorer prognosis in BC patients. These findings are consistent with a recent study which the upregulation of circPRMT5 in breast cancer cells contributes to the aggressive phenotype by mediating the miR-509-3p/TCF7L2 axis to activate the PI3K/AKT pathway [32]. Apart from that, our study further demonstrated that circPRMT5 is indispensable for the invasion and migration capabilities of BC cells.…”
Section: Discussionsupporting
confidence: 93%
“…High expression of circPRMT5 is associated with a poorer prognosis in BC patients. These findings are consistent with a recent study which the upregulation of circPRMT5 in breast cancer cells contributes to the aggressive phenotype by mediating the miR-509-3p/TCF7L2 axis to activate the PI3K/AKT pathway [32]. Apart from that, our study further demonstrated that circPRMT5 is indispensable for the invasion and migration capabilities of BC cells.…”
Section: Discussionsupporting
confidence: 93%
“…Due to this closed-loop structure, to some extent, it helps circRNA resist degradation by RNase, which highlights the advantages of circRNAs as a stable molecular biomarker for diverse cancers [5][6][7]. circRNAs are also crucial regulators in cancer biology [8][9][10]. For example, circ-PRMT5 aggravates the malignant characters of breast cancer cells by activating the PI3K/AKT pathway and up-modulating TCF7L2 expression [8].…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs are also crucial regulators in cancer biology [8][9][10]. For example, circ-PRMT5 aggravates the malignant characters of breast cancer cells by activating the PI3K/AKT pathway and up-modulating TCF7L2 expression [8]. So far, there are few researches on circ_0001287, and its role in NSCLC has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…7 The functions of circRNAs are coming into focus, and increasing evidence has shown that circRNAs play key regulatory roles in diverse cellular processes, such as cell proliferation, apoptosis, differentiation, and invasion. 8 In addition, several remarkable characteristics of circRNAs, including stability, 9 specificity, 10 conservatism, 11 and universality, 12 have been identified as potential biomarkers for diagnostics and as therapeutic targets in diseases, 13 such as ciRS-7 in Alzheimer's disease, 14 circ-PRMT5 in breast cancer, 15 hsa_circ_0000658 in osteosarcoma, 16 circRIMS1 in bladder cancer, 17 and circVMA21 in intervertebral disc degeneration. 18 Since 2015, the number of studies on circRNAs in OA has been increasing, and related publications have predominantly originated from China (Figure 1).…”
Section: Introductionmentioning
confidence: 99%